PENGARUH SELF-CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Nurul Fitayanti; Ana Rahmawati; Tafsillatul Mufida Asriningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research includes a combination research (mix method) with the type of concurered embedded, quantitative methods as the primary method used to test the effect of self-confidence on students' mathematical problem solving abilities statistically. followed by a complementary method, namely a qualitative method which is used to further analyze the effect of self-confidence on students' problem-solving abilities. The data collection techniques used were self-confidence questionnaire, KPMM test, and interview technique. While the data analysis techniques were quantitatively and qualitatively. Results of this study are (1) self-confidence affects students' mathematical problem solving abilities, (2) self-confidence affects students' mathematical problem solving abilities by 26.6%, (3) in general, subjects with self-confidence students have high and low levels of mathematical problem solving abilities. Subjects with moderate self-confidence have low and very low abilities in solving mathematical problems. Meanwhile, subjects with low self-confidence are also very low in solving mathematical problems.